Improving the Ability to Recognize the Letters through the Interactive Video Media "Mari Mengenal Huruf" in Group A Kindergarten: Meningkatkan Kemampuan Mengenal Huruf Abjad Melalui Media Video Interaktif “Mari Mengenal Huruf” Pada Anak Kelompok A di TK - Nur Amalina Cahyani; Luluk Iffatur Rocmah (Academia Open, 2021)
Cognitive ability is one of the developmental aspects of children who are experiencing maturity and need to be developed. In the cognitive development of early childhood there is one development that must be developed, namely recognizing letters. The introduction of the letters of the alphabet in early childhood helps children to recognize various kinds of letters of the alphabet. Regarding the letter recognition program, it can be done using interactive video media "Let's Get to Know the Letters". The purpose of this study was to improve the ability to recognize letters of the alphabet in Group A children in PKK 1 Jodokan Kindergarten, Beji District. This research is a Classroom Action Research. Based on the data analysis carried out, it was concluded that the ability to recognize the letters of the alphabet in group A in Pre-cycle obtained an average value of 35%, while in Cycle I the percentage was 48.33%, which means less than the maximum. Then giving the Cycle II action, the percentage of the average value becomes 93%, so that the average gain in cycle I and cycle II has increased again by 44.67%. The conclusion of this research is that through viewing the interactive video "Let's Get to Know the Letters" can increase the ability to recognize the letters of the alphabet.